The effect of soil tillage and nutrient supply on maize yield based on multi-year experimental results - Ragán, Péter; Rátonyi, Tamás; Fejér, Péter; Harsányi, Endre; Balláné Kovács, Andrea; Gumisiriya, Costa; Nagy, János; Sojnóczki, István; Tamás, András (Precision Crop Production, 2025)
To optimize maize (Zea mays) yield, soil tillage and nutrient supply play a key role. The application of appropriate soil tillage techniques and the precise application of nutrients can contribute to increasing yield, maintaining plant health, and developing sustainable agricultural practices. The aim of the study was to analyse the long-term yield performance of maize hybrids under different nutrient supply levels and basic tillage methods. According to the repeated measurement model, soil tillage, fertilization, and crop year had a significant (p<0.001) effect on maize yield. The integrated approach allows for the optimization of yield and the development of sustainable agricultural practices. Reduced soil tillage methods reduce soil erosion and improve soil biological activity.